PERAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA PEKANBARU DALAM PENGAWASAN TERHADAP PENANGANAN COVID-19 TAHUN 2021: PERSPEKTIF UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH: The Role of The Pekanbaru City Regional Representative Council (DPRD) In Supervision of The Handling of Covid-19 in 2021: Perspective of Law Number 23 Of 2014 Concerning Regional Government - Mahardhika, Made Bellisky; Wiratno (AMICUS CURIAE, 2024)
As a unitary state governed by the 1945 Constitution, Indonesia places a strong emphasis on regional government as an essential component of state administration. The focal point of this examination is to portray the administrative capability of the Pekanbaru City DPRD with respect to the treatment of Coronavirus in 2021 in view of Regulation Number 23 of 2014 concerning Provincial Government. The examination results show that the DPRD's job in observing the exhibition of the Pekanbaru City Territorial Government isn't completely in accordance with the assumptions and states of the pandemic around then. Despite the fact that it is obviously managed in regulation, DPRD actually faces different inward and outer difficulties that influence the viability of their oversight. These difficulties remember snags for coordination between individuals, interests among groups, and an absence of contribution in making extraordinary guidelines connected with Coronavirus. Regardless of this, the Pekanbaru City DPRD has followed the vast majority of the arrangements in Regulation 23 of 2014, however there are still viewpoints connected with follow-up to monetary review results that are not yet ideal because of restricted data got.